Trifluoromethylated fullerenes and polycyclic aromatic hydrocarbons and anaerobically milled silicon nanoparticles - Castro, Karlee P., author; Strauss, Steven H., advisor; Reynolds, Melissa M., committee member; Farmer, Delphine K., committee member; McCullagh, Martin J., committee member; Ramsdell, Howard S., committee member (Colorado State University. Libraries, 2015)
Well characterized molecules and materials are essential to understand trends and predict future performance. Fundamental studies provide information about molecular properties which may be useful in other applications such as electronic devices. The focus of this dissertation is the characterization of three different classes of molecules/materials with the goal of understanding the fundamental underlying reasons for any trends observed. The first chapter of this dissertation examines the photophysical properties of C70(CF3)n (n = 8 or 10) molecules. Four of the compounds exhibited quantum yields higher than for any previously reported C70 derivative and three exceeded 0.24, the highest fluorescence quantum yield for any fullerene or fullerene derivative. A difference in the location of only one CF3 group in C70(CF3)8 and C70(CF3)10 isomers resulted in 200-fold and 14-fold increases in fluorescence quantum yields respectively. The isomer of C70(CF3)10 with the highest fluorescence quantum yield (0.68 in toluene) also exhibited the longest fluorescence lifetime (51 ns). Formation of the S1 state in one of the C70(CF3)10 isomers occurred within 0.6 ps and its nanosecond-long decay was monitored by ultrafast transient absorption spectroscopy. Time-dependent density functional theory calculations provide a physically meaningful understanding of the photophysical properties. High fluorescence quantum yields are correlated with high oscillator strengths for the S0→S1 transition, large ΔS1−T1 energy gaps, and small spatial extension of the S0→S1 excitation. The second chapter of this dissertation explores trifluoromethyl derivatives of polycyclic aromatic hydrocarbons (PAH(CF3)n). First, the effects of PAH size and shape on the product distribution are examined. Second, the electronic properties, including reduction potential and gas-phase electron affinity, are examined. Third, the influence of number and orientation of the CF3 groups on the crystalline morphologies of these compounds is explored. Finally, charge-transfer complexes made with PAH(CF3)n molecules mixed with PAHs are prepared and examined spectroscopically and crystallographically. From this work it was determined that when PAHs with 8–10 substitutable carbons are reacted with at least 10 equivalents of CF3I gas the PAH(CF3)n products had n values of 4–6 regardless of the size or shape of the PAH core. The reduction potential and gas-phase electron affinity exhibit a regular, incremental increase as a function of the number of trifluoromethyl groups. The number and position of CF3 groups influences the π-π stacking and crystalline morphologies and typically the more CF3 groups added, the lower the intermolecular overlap. Charge-transfer complexes made from mixing PAH(CF3)n and PAH form mixed stacks in the solid-state and exhibit weak association constants in solution. The third chapter of this dissertation examines the effects of oxygen and aromatic molecules on stirred media milling of silicon. Metallurgical-grade silicon was wet-milled in a stirred media mill to produce nanoparticles. Several milling fluids, additives, and milling parameters have been tested and compared between aerobic and anaerobic milling. It was determined that oxygen and aromatic molecules serve as surface passivating additives and lead to higher specific surface areas, indicating smaller particles. Particle amorphization occurs rapidly in a stirred media mill, within two hours crystallite size is on the order of 2-50 nm regardless of whether surface passivating additives are present. In all milling experiments, even in the presence of oxygen, new Si–C bonds are formed, the most Si–C bonds are formed when aromatic molecules are present during the milling process.
Keywords: electron acceptor; fullerene; polycyclic aromatic hydrocarbon; silicon; trifluoromethyl